How the Promotional Strategies and Innovations of Korean Halal Products Featured in Korean Dramas Can Influence The Purchase Decisions and Consumer Interest - Anggeraini, Ria; Junaidi, Heri; Maulana, Chandra Zaki (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2024)
This study aims to analyze the impact of promotion and innovation of Korean Halal Products in Korean dramas on purchasing decisions through consumer interest in Palembang City. The research method employed a quantitative approach with statistical analysis using SmartPLS 4. Primary data was collected from respondents in Palembang City. The analysis results indicate that promotion and innovation of Korean Halal Products in Korean dramas significantly influence purchasing decisions positively. Furthermore, promotion and innovation also significantly affect consumer interest in these products. These findings suggest that promotions and innovations through Korean drama media play a crucial role in enhancing purchasing decisions and consumer interest in Korean Halal Products in Palembang City. The conclusions from this study support the theory that promotion and innovation play a role in influencing consumer behavior regarding purchasing decisions and interest in halal products. The practical implications of this research can assist marketing practitioners in planning effective promotion strategies for marketing Korean Halal Products in the Indonesian market, particularly in Palembang City.